Phenotypic delineation of the retinal arterial macroaneurysms with supravalvular pulmonic stenosis syndrome. Issue 3 (2nd December 2019) - Alkuraya, Hisham; Patel, Nisha; Ibrahim, Niema; Al Ghamdi, Bandar; Alsulaiman, Sulaiman M.; Nowilaty, Sawsan R.; Abboud, Emad; Alturki, Ramadan; Alkharashi, Abdullah; Eyaid, Wafaa; Almasseri, Zainab; Alzaidan, Hamad; et al.
Abstract: Retinal arterial macroaneurysms with supravalvular pulmonic stenosis (RAMSVPS), also known as Familial Retinal Arterial Macroaneurysms (FRAM) syndrome, is a very rare multisystem disorder. Here, we present a case series comprising ophthalmologic and systemic evaluation of patients homozygous for RAMSVPS syndrome causative IGFBP7 variant. New clinical details on 22 previously published and 8 previously unpublished patients are described. Age at first presentation ranged from 1 to 34 years. The classical feature of macroaneurysms and vascular beading involving the retinal arteries was universal. Follow up extending up to 14 years after initial diagnosis revealed recurrent episodes of bleeding and leakage from macroaneurysms in 55% and 59% of patients, respectively. The majority of patients who underwent echocardiography (18/23) showed evidence of heart involvement, most characteristically pulmonary (valvular or supravalvular) stenosis, often requiring surgical correction (12/18). Four patients died in the course of the study from complications of pulmonary stenosis, cerebral hemorrhage, and cardiac complications. Liver involvement (usually cirrhosis) was observed in eight patients. Cerebral vascular involvement was observed in one patient, and stroke was observed in two. We conclude that RAMSVPS is a recognizable syndrome characterized by a high burden of ocular and systemic morbidity, and risk of premature death. Recommendations are proposed for early detection and management of these complications. Abstract : Retinal arterial macroaneurysms with supravalvular pulmonic stenosis (RAMSVPS).